EDUCATOR INDUCED POST TRAUMATIC STRESS DISORDER (EIPTSD) IN A 6 YEAR OLD BOY - Saman, Iqbal; Syed , Ehsanullah (Journal of Pakistan Psychiatric Society, 2006)
Post-traumatic stress disorder (PTSD) is a delayed and/or protracted response to exceptionally threatening or catastrophic events. The event is persistently remembered or relived with concomitant distress sometimes even leading to harmful life-long psychological sequelae. We present a 6-year old boy who developed the classical syndrome following corporal punishment at school when his class teacher injected an empty syringe into his gluteal region. Keywords :Post-traumatic stress disorder, trauma, stressor, corporal punishment